A hyper-heuristic with two guidance indicators for bi-objective mixed-shift vehicle routing problem with time windows - Chen, Binhui; Qu, Rong; Bai, Ruibin; Laesanklang, Wasakorn (Springer, 2018)
In this paper, a Mixed-Shift Vehicle Routing Problem is proposed based on a real-life container transportation problem. In a long planning horizon of multiple shifts, transport tasks are completed satisfying the time constraints. Due to the different travel distance and time of tasks, there are two types of shifts (long shift and short shift) in this problem. The unit driver cost for long shifts is higher than that of short shifts. A mathematical model of this Mixed-Shift Vehicle Routing Problem with Time Windows (MS-VRPTW) is established in this paper, with two objectives of minimizing the total driver payment and the total travel distance.